Pathologies of intersubjectivity in autism and schizophrenia - Fuchs, Thomas (Journal of consciousness studies, 2015)
Most mental disorders include more or less profound disturbances of intersubjectivity, that means, a restricted capacity to respond to the social environment in a flexible way and to reach a shared understanding through adequate interaction with others. Current concepts of intersubjectivity - are mainly based on a mentalistic approach, assuming that the hidden mental states of others may only be inferred from their external bodily behaviour through 'mentalizing' or 'mindreading'. On this basis, disorders of intersubjectivity for example in autism or schizophrenia - are attributed to a dysfunction of Theory of Mind modules. From a phenomenological point of view, however, intersubjectivity is primarily based on a pre-reflective embodied relationship of self and other in an emergent bipersonal field. Instead of a theory deficit, autistic and schizophrenic - patients rather suffer from a basic disturbance of being-with-others which they try to compensate by explicit inferences and hypothetical assumptions about others. The paper consequently distinguishes three levels of intersubjectivity: (a) primary intersubjectivity or intercorporeality, (b) - secondary intersubjectivity or perspective-taking, and (c) tertiary intersubjectivity, implying a self-other metaperspective. On this basis, disturbances on these different levels in autism and schizophrenia are described.